Roughness Effects of Textured Surfaces in Hydrodynamic Lubrication - Youssef Bahi; Mhammed El Gadari; Miloud Rahmoune (International Journal of Applied Mechanics and Engineering, 2022)
Several studies have been conducted to improve and model the lubricated contact between surfaces. The main subjects were defining the hydrodynamic parameters to reduce energy losses and protect the environment. Some of the proposed models have studied the effect of textures in hydrodynamic lubrication and have proved that adapted shapes and geometries can improve the performance of lubricated contacts. A hydrodynamic model was developed by assuming the roughness of the textured surface and considering the cavitation in a steady-state regime. The proposed model was validated and compared with the analytical model of Fowell et al. [1]. Three different textures shapes were considered. The results showed that the rough-textured thrust affects the hydrodynamic performance significantly. Thus, by increasing the arithmetic roughness of textured surfaces, the hydrodynamic pressure, and the lifting force increase depending on the texture shape. A rougher surface slightly increases the friction force for the three considered textures.